Palm Oil Utilization (Palm Waste) - Yusup, Suzana (Nova Science Publishers, 2011)
Utilization of palm based material to produce bio-energy and bio-chemical has gain prime attention recently due to environmental concern and sustainability issues of the environment. Malaysia is one of the largest producers of palm oil which is mainly used in food related industries worldwide and on a smaller scale as basic raw material for soap processing. Usage of its fibers and shell from the processing waste as its fronds and trunks has the potential to be converted to alternative fuel i.e. bio-fuel or bio-chemicals. The chapter covers topics on acts and policies on biomass as renewable energy in Malaysia, utilization of palm waste from palm based materials to produce bio-energy and bio-chemicals and the associated processing technology, characterization of palm wastes, logistics and quality control of palm wastes and modelling of biomass processing system. Attention is given particularly to the utilization of biomass in Malaysia in addition to country such as Indonesia for comparative purposes. Technologies to convert biomass to bio-energy in form of solid, liquid and gaseous fuel and bio-chemicals are also discussed. These cover processes such as torrefaction, pelletisation, gasification, fast pyrolysis for conversion of lignocellulosic materials. The chemical energy content of the harvested palm fruit and biomass exceeds the energy input through the farming systems due to the conversion of solar radiation to plant growth by photosynthesis. Thus oil palm can act as a net source of useful energy. Method to estimate amount of energy generated from biomass processing is highlighted.